Efek Samping Regulasi Terkait ENDC (Enhanced Nationally Determined Contribution) terhadap Kemunculan Praktik Greenwashing oleh Pelaku Usaha di Indonesia [Side Effects of Regulations Related to ENDC (Enhanced Nationally Determined Contribution) on the Emergence of Greenwashing Practices by Business Actors in Indonesia] - Raodah, Putri; Siddiq, Nakzim Khalid; Taufik, Zahratulain (UKInstitute, 2026)
Greenwashing practices are carried out by businesses with unsubstantiated sustainability claims. The purpose of this research is to analyze the regulatory framework for business obligations in achieving Indonesia's 2022 ENDC target and the legal consequences of greenwashing. The research uses normative methods, conceptual approaches, and legislation. Law 16/2016, the ratification of the Paris Agreement, is the legal basis for the state's obligation to reduce emissions. Presidential Regulation 98/2021, the legal basis for the state, divides obligations among businesses, making them essential actors in achieving Indonesia's ENDC target. Ministerial Regulation of the Environment and Forestry 21/2022, the legal basis, contains operational procedures for businesses in carrying out their obligations through the SRN-PPI emission data instrument. The legal consequences arising from greenwashing practices as a side effect of Indonesia's ENDC regulations include articles in each law on competition and consumer protection that direct action against businesses engaging in greenwashing. However, adjustments to legislation and institutions that guarantee the credibility and oversight of GHG emission data are needed. Abstrak. Praktik greenwashing dilakukan oleh pelaku usaha dengan klaim berkelanjutan yang tidak berdasar. Tujuan penelitian adalah untuk menganalisis kerangka regulasi kewajiban pelaku usaha dalam mencapai tareet ENDC Indonesia 2022 dan konsekuensi hukum efek samping Greenwashing. Penelitian menggunakan metode Normatif, pendekatan konseptual dan perundang-undangan. Undang-undang 16/2016, ratifikasi Paris Agreement dasar hukum kewajiban negara mengupayakan penurunan Emisi. Perpres 98/2021, dasar hukum negara membagi kewajiban kepada pelaku usaha, sehingga pelaku usaha menjadi aktor esensial dalam mencapai target ENDC Indonesia. Permen LHK 21/2022, dasar hukum berisi prosedur operasional bagi pelaku usaha dalam melaksanakan kewajibannya melalui instrument data emisi yaitu SRN-PPI. Konsekuensi Hukum yang Timbul dari Praktik Greenwashing Sebagai Efek Samping Regulasi ENDC Indonesia adalah masing-masing undang-undang persaingan usaha dan perlindungan konsumen telah memiliki pasal-pasal yang mengarah pada penindakan pelaku usaha yang melakukan Greenwahing. Akan tetapi penyesuaian perauturan perundang-undangan dan kelembagaan yang menjamin kredibilitas dan pengawasan data Emisi GRK.